Pemberdayaan Kelompok Wanita Tani Prabumulih melalui Workshop Studi Kelayakan Bisnis: Pengabdian - Marieska Lupikawaty; Neneng Miskiyah; Martha Aznury; Anerasari Meidinariasty (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program empowered the Kemuning Women Farmers Group (KWT) in Prabumulih through a Business Feasibility Study Workshop to address managerial challenges and enhance business sustainability. A participatory approach was applied to build technical capacity in five areas: (1) basic financial management, (2) digital marketing strategies using WhatsApp, (3) optimizing limited land production through recycled hydroponics and tiered polybag cultivation, (4) human resource management based on skill mapping, and (5) structured risk mitigation. Collaboration among PT Pertamina EP Prabumulih Field, Sriwijaya State Polytechnic, and the local government was key to success. Outputs included operational documents and behavioral changes in business management. Evaluation showed improved KWT capacity in financial feasibility, production efficiency, and risk readiness, transforming the business model from subsistence to sustainable women’s agripreneurship.